2019
DOI: 10.1186/s12906-019-2502-z
|View full text |Cite
|
Sign up to set email alerts
|

Mind-body practices for people living with HIV: a systematic scoping review

Abstract: Background Mind-body practices are frequently used by people living with HIV to reduce symptoms and improve wellbeing. These include Tai Chi, Qigong, yoga, meditation, and all types of relaxation. Although there is substantial research on the efficacy of mind-body practices in people living with HIV, there is no summary of the available evidence on these practices. The aim of this scoping review is to map available evidence of mind-body practices in people living with HIV. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 141 publications
(436 reference statements)
0
21
0
2
Order By: Relevance
“…26 Finally, a systematic scoping review of 84 studies showed that mindfulness, relaxation techniques, cognitivebehavioral strategies, and yoga had beneficial effects on health-related quality of life and physical and psychological symptoms among PLWH. 18 Emerging evidence also suggests that mind-body exercise can improve physical performance among PLWH. Participants in the abovementioned RCT by Galantino and colleagues (2005) who performed aerobic exercise and Tai Chi had significant improvements in balance using the functional reach test.…”
mentioning
confidence: 99%
“…26 Finally, a systematic scoping review of 84 studies showed that mindfulness, relaxation techniques, cognitivebehavioral strategies, and yoga had beneficial effects on health-related quality of life and physical and psychological symptoms among PLWH. 18 Emerging evidence also suggests that mind-body exercise can improve physical performance among PLWH. Participants in the abovementioned RCT by Galantino and colleagues (2005) who performed aerobic exercise and Tai Chi had significant improvements in balance using the functional reach test.…”
mentioning
confidence: 99%
“…CRGT may offer participants practical and emotional coping strategies alongside the inherent social connection benefit that participants can receive from the mutual aid control. This will build on existing research showing that combination approaches are preferable to people living with HIV22 and people with dementia,19 while addressing the gap in psychosocial interventions for people with HAND. This refinement pilot trial will provide insight into the feasibility and acceptability of CRGT and a study of this nature, to inform the development of a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population with dementia, a systematic review synthesis found that these group-based, multicomponent strategies improve global cognitive functioning and activities of daily living to a greater extent than a single-component therapy 21. Similar evidence for people living with HIV is still emerging; however, a recent scoping review found that combination approaches (ie, mindfulness, cognitive training techniques and group therapy) to psychosocial interventions may have better health outcomes for people living with HIV than a single technique approach 22. People with the emotional stability and practical coping strategies can more successfully adapt to the challenges of ageing, such as cognitive decline 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…129 Successful applications include menopausal transition, 130 autism, 131 posttraumatic stress disorder, 132 musculoskeletal pain, 133 hearth failure, 134 and helpful for people living with HIV. 135 Yoga and meditation. Yoga is an ancient Indian therapy based on undergoing to a "yoke" for balancing the body and mind through positions and stretching's in order to heal or transcend to a higher level for pediatric and medical conditions, including a very ample spectrum of diseases.…”
Section: Mind-body Manipulation Therapiesmentioning
confidence: 99%